Mindfulness-based interventions in undergraduate students: a systematic review - Chiodelli, Roberto (2021)
Objective: To describe how mindfulness-based intervention (MBIs) are held with undergraduate students, systematize the outcomes of these interventions and indicate possible limitations. Method: Systematic searches were performed in seven databases in January 2019 with the following descriptors: ("mindfulness intervention" AND ("undergraduate" OR "college" OR "students"). Results: A total of 510 articles were found, and 19 articles fully met the inclusion criteria. The searches showed a visible growth in this field of research as articles publications increased in the past years. Regardless of intervention's length, most studies reported beneficial effects. The examination of Anxiety, Stress, and Depression constructs have shown to be predominant. Even though study designs were mostly randomized controlled trials (RCT), it was noticed a shortage use of physiological measures and follow-up assessments. Conclusions: Nonetheless, MBIs have shown to be promising interventions to promote mental health in academic settings.